Polarization-resolved surface-enhanced sensing of single-stranded DNA with Bloch surface waves - Mogni Erika; Pellegrini Giovanni; Gil-Rostra Jorge; Yubero Francisco; Celebrano Michele; Finazzi Marco; Schmidt Katharina; Fossati Stefan; Biagioni Paolo; Dostálek Jakub (EPJ Web of Conferences)
We describe a novel one-dimensional photonic crystal design allowing for the concurrent excitation of transverse-electric and transverse-magnetic Bloch surface waves, thus paving the way for polarization-resolved sensing experiments. We discuss its application for the surface-enhanced sensing of oriented DNA molecules through nanoscale birefringence measurements.